2018
DOI: 10.1016/j.ygcen.2017.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age-class and social context on fecal glucocorticoid metabolite levels in free-ranging male giraffes

Abstract: One of the primary sources of perceived stress is the social environment of an animal and the interactions with conspecifics. An essential component of the response to a stressor is the activation of the hypothalamic-pituitary-adrenocortical axis, which results amongst others in a temporal increase in circulating glucocorticoid (GC) levels. Giraffes occur in a highly flexible fission-fusion social system and group compositions can change on a daily basis, with bulls establishing an age-related dominance hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
(74 reference statements)
0
22
0
Order By: Relevance
“…Age-dependent differences in GCs have been found in other mammals, e.g., free-ranging younger male giraffe (Giraffa camelorpadalis giraffa) bulls had higher FGM concentrations when compared to older age classes [14], while older wild grey mouse lemurs (Microcebus murinus) showed higher FGM concentrations [20]. It should be noted that those effects were dependent on social context and season [14,20] and that interpretations of FGM concentrations are often highly context-dependent [71,72]. A study on Asian elephants from tourist camps from Thailand found a strong trend between age and FGM concentrations, with older elephants having lower FGM concentrations [73].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Age-dependent differences in GCs have been found in other mammals, e.g., free-ranging younger male giraffe (Giraffa camelorpadalis giraffa) bulls had higher FGM concentrations when compared to older age classes [14], while older wild grey mouse lemurs (Microcebus murinus) showed higher FGM concentrations [20]. It should be noted that those effects were dependent on social context and season [14,20] and that interpretations of FGM concentrations are often highly context-dependent [71,72]. A study on Asian elephants from tourist camps from Thailand found a strong trend between age and FGM concentrations, with older elephants having lower FGM concentrations [73].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, stress can occur when suffering from a disease, when confronted with dominant conspecifics (social stress), or when experiencing extreme environmental situations that threaten homeostasis [11][12][13]. In addition, various internal and external factors can affect stress or stress responsiveness in animals, such as age [14,15], sex [16][17][18], and ecological conditions [19][20][21], or even positive challenges such as breeding interactions, and interpreting stress hormone concentrations is therefore not always straightforward [22,23] and can be context-dependent [24]. Nevertheless, how well an animal can cope with threatening situations is generally reflected by its stress response and therefore, measuring stress can be a useful biomarker to assess the health or well-being of animals.…”
Section: Introductionmentioning
confidence: 99%
“…As known from other studies investigating fecal glucocorticoids, the total amount of excretion may differ largely owing to environment temperature, species, collection, cage tape, time, capacity, reproductive condition, season, social and so on (Huber et al 2003;Frigerio et al 2004;Hunt and Hambly 2006;Thanos et al 2009;Su et al 2014a/b? ;Cornale et al 2016;Dantzer et al 2016;Mendonça-Furtado et al 2017;Pineda-Galindo et al 2017;Sipari et al 2017;Łopuckia et al 2018;Wolf et al 2018). Therefore, the aim of our study was to gain information about the effect of RH at acute and chronic moderate Ta on growth performance and total amount of droppings' corticosterone metabolites of broilers, since this knowledge is essential to develop, establish, and successfully apply techniques to monitor stress hormones non-invasively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the total amount of droppings' corticosterone metabolites were positively correlated with plasma corticosterone, indicating that droppings' corticosterone metabolites could also be used to diagnose stress response (Bradely and Holmes 1971;Culbert and Wells 1975;Teskey-Gerstl et al 2000b;Dehnhard et al 2001). And it has been already used to investigate questions in the fields of "stress and animal welfare, reproductive, physiology, and behavioral ecology" (Turriani et al 2016;Yarnell et al 2016;Biancani et al 2017;Cao et al 2017;Webster et al 2017;Cinque et al 2018;Wolf et al 2018), such as fighting against spotted hyenas (Goymann et al 1999), drought or social stress on African elephants (Foley et al 2001), catching stress on laying hens (Fraisse and Cockrem 2006), mercury exposure to tern stress (Herring et al 2012), and heat stress on broilers ( Su et al 2014a/b? ).…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing giraffe population decline, now listed as Vulnerable in the Red List of Threatened Species (IUCN 2017), it is important to better understand the factors affecting giraffe welfare. As a key prerequisite, previous studies have demonstrated that non-invasive monitoring of stress hormone levels in the form of faecal glucocorticoid metabolites (fGCM) is feasible in giraffes (Bashaw et al 2016, Wolf et al 2018.…”
mentioning
confidence: 99%